2016
DOI: 10.1080/03736687.2016.1225777
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 49

Abstract: International audienceBryological Note

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 109 publications
(34 reference statements)
0
11
0
2
Order By: Relevance
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 89%
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 89%
“…Dumort. [77], Barbilophozia floerkei (F. Weber & D. Mohr) Loeske [78], and Cephaloziella rubella (Nees) Warnst. [79].…”
Section: Discussionmentioning
confidence: 99%
“…Bucklandiella didyma is panholantarctic temperate species having optimum occurrence in southern South America. It has a continuous geographical range in the Nothofagus Blume zone on the western fringes of the continent, extending from central Chile to Tierra del Fuego (Deguchi 1984), with some isolated stations in the Archipelago Juan Fernández, in Santa Catarina Province in SE Brazil (Bednarek-Ochyra et al 1999), the Falkland Islands (Ochyra, Crabtree, et al 2015) and on subantarctic South Georgia (Ellis, Agcagil, et al 2016). Outside South America, it has been reported from South Africa , Tasmania and New Zealand Blockeel, Bednarek-Ochyra et al 2010).…”
Section: Contributor H Bednarek-ochyramentioning
confidence: 99%
“…However, the latter two species differ from N. obtusifolia in having immersed stomata and recurved leaf margins (Plášek et al 2014;Sawicki et al 2017). Orthotrichum crenulatum is a Central Asian species, described from west Tibet and known from Shaanxi, Xinjiang, Xizang and Inner Mongolia Provinces in China, Afghanistan, Pakistan, Georgia, NE Turkey, Kyrgyzstan, Kazakhstan, Siberia, north India (Kashmir), central India, Turkestan, with an isolated locality in Japan (Lewinsky 1992;Lewinsky-Haapasaari 1996; Schäfer-Verwimp and Gruber 2002; Lara et al 2010; Ellis, Akhoondi, et al 2011;Ellis, Afonina, Asthana, et al 2014;Suzuki 2014;Alam et al 2015;Ellis, Agcagil, et al 2016;Fedosov et al 2017). In Russia, until now, it was only known to occur in xeric areas of Transbaikalia, Buryatia and Anabar Plateau, but was unknown from the western part of southern Siberia between eastern Buryatia and Kazakhstan, despite xeric landscapes suitable for this species being widespread throughout the area.…”
Section: Marchantia Paleaceamentioning
confidence: 99%